Acute effect of dual-task endurance exercise on cognitive functions and myocardial oxygen consumption; a randomized, controlled trial. - Atak, Ebrar; Ataç, Amine (Critical Public Health, 2025)
ABSTARCT: Dual-task exercise and its impacts on cognitive function have gained increasing attention in recent years. Targeted aerobic exercise, cardiovascular responses, and the associated improvements in cognitive performance appear promising for mitigating certain cognitive disorders, although the optimal protocol remains unclear. In this randomized controlled trial, 34 participants meeting inclusion criteria were allocated into either a standardized aerobic exercise group (BSAEgr, n = 18) or a dual-task aerobic exercise group (BIDAgr, n = 16). Cognitive status was assessed with the Montreal Cognitive Function Assessment Scale (MOCA), and reaction time performance was measured using the Nelson Reaction Test (NRT). Cardiovascular responses including systolic blood pressure, diastolic blood pressure, pulse rate, and the double product formula were evaluated before and after the intervention. The findings demonstrated that dual-task aerobic exercise led to greater improvements in cognitive function compared to standardized aerobic exercise. Significant improvements were observed in MOCA scores, NRT distance, and NRT outcome measures within the dual-task group (p < 0.005). These results provide preliminary evidence that incorporating dual-task elements into aerobic training may enhance both cognitive and cardiovascular outcomes, suggesting potential applicability in preventive and rehabilitative settings.